Lifestyle modification and selected pharmacological therapies in Polycystic Ovary Syndrome: current evidence and emerging approaches - Brzozowska, Agnieszka; Garbacz, Anna Izabela; Majszyk, Tomasz Julian; Głuski, Jacek; Borowiecka, Patrycja Anna; Węglarz, Aleksandra; Kosiorek, Paweł; Niezgoda, Ada; Olborska, Anna; Wrochna, Bartłomiej Maciej; et al. (Quality in Sport, 2026)
Background: Polycystic ovary syndrome (PCOS) is a common endocrine disorder in women of reproductive age, associated with hyperandrogenism, menstrual irregularities, infertility, insulin resistance, and increased cardiometabolic risk. Aim: The aim of this narrative review was to summarize current evidence-based therapies for PCOS management, focusing on lifestyle modification and selected pharmacological options. Materials and Methods: A literature search was conducted in PubMed using the term “Polycystic Ovary Syndrome (PCOS)” combined with the following keywords: “lifestyle”, “physical activity”, “exercise”, “diet”, “pharmacotherapy”, “treatment”, “metformin”, “fertility”, “GLP-1”, “inositol”, and “gut microbiota”. Articles published from 2019 onwards were included. Results: Lifestyle modification remains the first-line approach and may improve metabolic, hormonal, and reproductive outcomes. Pharmacotherapy is used as an adjunct when lifestyle measures are insufficient. Established options include metformin, combined oral contraceptives, antiandrogens in selected cases, and ovulation induction agents. Emerging evidence supports GLP-1 receptor agonists for obesity-related PCOS, although long-term data are limited. Inositol and gut microbiota-targeted strategies remain experimental. Conclusions: PCOS management should be individualized and long-term, combining lifestyle interventions with appropriate pharmacotherapy and patient education to improve adherence and outcomes.